Bifidobacterium animalis subsp. lactis HN019 Effects on Gut Health: A Review - Cheng, Jing; Laitila, Arja; Ouwehand, Arthur C. (Frontiers in Nutrition, 2021)
Optimal gut motility is central to bowel function and gut health. The link between the gut dysmotility related disorders and dysfunctional-intestinal barriers has led to a hypothesis that certain probiotics could help in normalizing gut motility and maintain gut health. This review investigates the roles of Bifidobacterium animalis subsp. lactis HN019 (B. lactis HN019™) on gut health, and its mechanisms of action in various pre-clinical and clinical studies. Research supports the hypothesis that B. lactis HN019™ has a beneficial role in maintaining intestinal barrier function during gastrointestinal infections by competing and excluding potential pathogens via different mechanisms; maintaining normal tight junction function in vitro and regulating host immune defense towards pathogens in both in vitro and human studies. This has been observed to lead to reduced incidence of diarrhea. Interestingly, B. lactis HN019™ also supports normal physiological function in immunosenescent elderly and competes and excludes potential pathogens. Furthermore, B. lactis HN019™ reduced intestinal transit time and increased bowel movement frequency in functional constipation, potentially by modulating gut-brain-microbiota axis, mainly via serotonin signaling pathway, through short chain fatty acids derived from microbial fermentation. B. lactis HN019™ is thus a probiotic that can contribute to relieving gut dysmotility related disorders.